A variação da concordância nominal de número em cartas de inábeis do sertão baiano: (1906-2000) - Santos, Lorena Enéas Rosa (2017)
This dissertation undertakes an analysis of variation in number agreement in the noun phrase in 91 personal letters, edited by Santiago (2012), written between 1906 and 2000 by semi-literate Bahian inlanders, defined as "unskilled" (MARQUILHAS, 2000). It is a very rare type of documentation, offering indications of the popular variant of Brazilian Portuguese (BP). The research takes as the theoretical scope the Historical Linguistics stricto senso, in the terms defined by Mattos and Silva (2008) and the Labovian Sociolinguistics (LABOV, 1972), for whom the change must be explained not only by internal arguments to the system, but also by the external. From the analysis of the data, the linguistic and social factors that most conditioned the variation were identified, from two perspectives: the syntagmatic and the atomistic. In addition, we verified if the linguistic behavior of the writers of the letters that integrate the corpus in question present similarities and/or divergences with the results of previous works about this subject in the popular BP, in oral and written corpus, and in the acquisition of agreement. The results showed that the strategies most used by unskilled scribes regarding to the realization of the plurality marks in the NP are close to both the popular BP variants and to the constructs found in acquisition studies. The linguistic study carried out here may contribute to the characterization of the spoken language in the semi-arid region of Bahia, collaborating in general for the study of popular Portuguese in Brazil and, more specifically, in the rural Portuguese of Bahia.